Spatiotemporal evolution and driving factors of urban green technology innovation efficiency in the Chengdu-Chongqing Economic Circle of China - Deng, Shicheng; Wu, Yuming (Frontiers in Ecology and Evolution, 2023)
Green technology innovation efficiency (GTIE) growth is an essential route to protect urban ecological environment in the Chengdu-Chongqing Economic Circle (CCEC). However, the measurement and spatial driving factors of GTIE are still puzzled. This study constructs an urban GTIE indicator system including inputs, desired outputs, and undesired outputs, and evaluates urban GTIE in the CCEC using the super-efficiency slacks-based measure (S-SBM). Then, the exploratory spatial data analysis (ESDA) method is applied to analyze the geographical distribution and spatial correlation characteristics of urban GTIE, and a spatial econometric model is used to analyze the influencing factors of urban GTIE from the perspective of spatial spillover. The results are as follows: (1) From 2006 to 2020, the urban GTIE of CCEC has obviously increased, and its spatial distribution has a prominent unbalanced feature. (2) The urban GTIE of CCEC mainly presents a significant spatial positive correlation, mainly manifested in the "high-efficiency type" and "low-efficiency type" regional agglomeration patterns, and the spatial "core-edge" structure centering on Chengdu and Chongqing tends to be stable. (3) Economic development (ED), government support (GS), and environmental regulation (ER) can promote the urban GTIE. The negative spillover effects of external opening (EO) and ER are significant, and they have negative effects on the GTIE of neighboring cities. (4) Spatial heterogeneity analysis shows that the driving factors of urban GTIE with different efficiency levels are significantly different, and the spatial spillover effect of the driving factors of GTIE is more significant in high-efficiency cities.